Pengaruh Kapasitor Shunt Terhadap Susut Transmisi Sistem Interkoneksi Sulselbar Berbasis DIgSILENT Power Factory 15.1. - Marwan, Marwan; Nurhayati, Nurhayati; A. Al Qahfi, Andi Sultan; Burhan, Rizqi A (Politeknik Negeri Ujung Pandang, 2016)
The aim of this research is to investigate the influence of shunt capacitor on losses of interconnection system of Sulselrabar transmission lines. In this study, DIgSILENT Power Factory 15.1 software is used to simulate the power flow in the system under study. There are three conditions applied in this study; real condition, in condition of all capacitors activated and in condition of all capacitors inactivated. Obtained results show that there are differences in the value of the losses among these three conditions, where the lowest losses is occurred at the second condition with 1,69% and the highest losses occurred at the third condition with 1,76%.